M5 positive allosteric modulation alleviates parkinsonian motor deficits - Nicole E. Chambers; Dominic Hall; Morgan Kaplan; Sarah Garan; Tyler Eichner; Mark S. Moehle (PLoS ONE, 2026)
Parkinson’s disease is a neurodegenerative movement disorder which is characterized by cardinal motor symptoms of tremor at rest, rigidity, bradykineasia, and postural instability. Underlying these cardinal motor symptoms is thought to be death and dysfunction of nigrostriatal dopamine neurons, and the gold-standard treatment of Parkinson’s disease is dopamine replacement therapy with the dopamine precursor L-DOPA. While efficacious, L-DOPA does not treat all motor symptoms and can have serious treatment-related side effects called L-DOPA induced dyskinesias, indicating an immense need for new targets to modulate dopaminergic function for anti-parkinsonian efficacy. One such potential target is the M 5 muscarinic acetylcholine receptor, which has a unique expression profile where it is selectively expressed in midbrain dopaminergic neurons and their terminals in the striatum, and previous studies have indicated that M 5 can modulate dopamine release and patterning of firing of dopamine neurons. Given this unique expression profile and function of M 5 , this receptor has an untested potential to modulate parkinsonian motor phenotypes. To test the potential for M 5 to modulate Parkinsonian-like motor deficits and dyskinesia, we employed the unilateral 6-OHDA lesioned mouse model to create a hemi-parkinsonian state. Using multiple behavioral assays, including the cylinder test, forepaw adjusting steps assay, and in the Erasmus ladder, in conjunction with prototypical M 5 pharmacological tool compounds, we investigated the ability of M 5 to modulate parkinsonian motor deficits. Additionally, we tested the ability of M 5 to modulate established L-DOPA induced dyskinesia or cause dyskinesia on its own. Overall, we found that M 5 PAM alleviates forepaw asymmetry, bradykinesia, and spatial aspects of gait in the Erasmus ladder. Excitingly, M 5 PAM does not cause robust dyskinesia, does not affect already established L-DOPA-induced dyskinesia, and does not affect L-DOPA motor efficacy. Taken together with previous findings, the current study suggests that M 5 receptors are an exciting novel therapeutic strategy for ameliorating parkinsonian motor deficits even in late-stage models of severe PD without lessening L-DOPA’s motor benefit and without affecting existing symptoms of L-DOPA-induced dyskinesia.